The BANI Framework and Indonesian Diplomatic Communication: A Critical Discourse Analysis of the Indonesian Ministry of Foreign Affairs - Algooth Putranto; Khairul Syafuddin (Ikatan Sarjana Komunikasi Indonesia, 2026)
This study highlights the discourse constructed by the Indonesian Ministry of Foreign Affairs (MoFA) in demonstrating its role through digital diplomacy. Through these efforts, MoFA Indonesia adapts a digital diplomacy strategy to maintain public trust and national stability amidst global fragility and anxiety. The purpose of this study is to analyze the contemporary diplomatic communication forms of MoFA Indonesia in building cooperation between countries and the crisis communication strategies implemented through its official YouTube channel. This research uses a qualitative approach with a case study research type. The analytical technique used is critical discourse analysis with the Fairclough approach. This study examines MoFA Indonesia's video content related to the context of crises and bilateral cooperation. The analysis results show that MoFA Indonesia implements a two-track communication strategy: reactive diplomacy and proactive diplomacy. Reactive diplomacy is carried out in crisis situations to calm public anxiety and demonstrate state control. Meanwhile, proactive diplomacy is carried out in the realm of bilateral cooperation to build long-term resilience against global uncertainty. Both utilize digital platforms to control the narrative, target multiple audiences, and project the state's competence. Theoretically, this study expands digital diplomacy literature by establishing the BANI (Brittle, Anxious, Non-linear, and Incomprehensible) framework as a superior analytical tool for mapping state communicative responses to non-linear and incomprehensible global disruptions, providing a deeper conceptual understanding of narrative resilience beyond the conventional VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) paradigm.